(untitled) (Revista científica Olimpia, 2020)
The families of some athletes have little influence on group creativity to their members, a situation that threatens the sporting success of its members. This is largely due to the fact that the family as a primary group generates little stimulation of creativity within coexistence. Hence, this study has as its general objective: to propose a psychoeducational intervention program to stimulate group creativity in families of high-performance athletes from the EIDE Pedro Batista Fonseca. He used as methods: observation, interview, document analysis and action research. This materialized from the phases of: diagnosis, problematization, design of the change proposal, application of the same and its respective evaluation. Thus, a better level of awareness and scope of group creativity was identified from the fluency of ideas in the solution to conflictive family situations that arise unexpectedly, flexibility in the ways of specifying the rules and regulatory requirements of the home, originality versus to breakages of equipment and objects in the home; and group cooperation that takes shape in the zone of proximal development with activities not dominated by some and frequently exercised by others. These results allowed demonstrating that group creativity is possible in the family environment, despite the strong resistance to change, which is uncritically experienced in the reality of homes and in psychoeducational intervention.